The Effect of Machiavellianism on Employee Resistance to Change: The Mediation of Employee Needs - Janah, Nila Raudlotul; Nuzulia, Siti (Universitas Muhammadiyah Sorong, 2024)
In today's organizational environment, the ability to survive the demands and change is the key to a company's success. However, the main problem faced by companies in implementing change is resistance from their employees although there have been many previous studies that discuss organizational dimensions in increasing employee acceptance. Therefore, this article discusses the relationship of employees' Resistance to Change with Machiavellianism and mediating role of Manifest Needs, which consists of Need for Dominance, Need for Achievement, Need for Autonomy, and Need for Affiliation. Data from 259 employees have been collected from various companies in Indonesia. The results obtained showing that Need for Autonomy significantly mediates the relationship between Resistance to Change and Machiavellianism as well as contributes to the theory while filling the research gap. In addition, this research also discusses recommendations for the future research and limitations associated with this research.